Use of external quality assessment in extra-analytical phases in clinical laboratories in Spain: a survey by the Spanish Society of Laboratory Medicine (SEQCML) - Caballero Garralda Andrea; Reixach Immaculada Comas; García Miralles Carlos; Gómez Rioja Rubén; Llopis Díaz María Antonia; Martínez Espartosa Débora; Nicolás de Blas Reyes; Panadès Turró Mariona; Puigví Fernández Laura; Rodelgo Jiménez Laura; Sufrate-Vergara Berta; Ventura Orriols Emma (Advances in Laboratory Medicine)
Quality indicators (QIs) are a valuable tool for monitoring and improving extra-analytical phase performance in the clinical laboratory (CL). For that reason, the Spanish Society of Laboratory Medicine (SEQCML) launched its Pre-analytical Phase EQA Program in 2001.